USULAN PERBAIKAN AREA KERJA MENGGUNAKAN METODE 5S GUNA TAHAP AWAL PENERAPAN LEAN MANUFACTURING (STUDI KASUS PT. XYZ) - Dika Priyanto; Indro Prakoso (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
PT. XYZ is a company engaged in wood processing. The product produced is plywood according to customer demand. After observing the production floor, several problems were found, namely that there was unused equipment in the work area. This equipment is equipment that is damaged or is not used. Besides, the cleanliness of the production floor is also poorly maintained where there is still dirt and dust. This study aims to identify problems related to waste on the production floor and design and propose the 5S method to create an effective work environment. The method used in this study uses the 5S concept approach (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). 5S assessment is carried out using the audit checklist and evaluation checklist. The audit checklist and evaluation checklist are filled out by an auditor who knows clearly how the actual conditions on the production floor are. Data were collected in five work areas, namely rotary, press dryer, repair, assembling, and packing. The results of this study can be concluded that 1) problems on the production floor of PT XYZ include: there is no written procedure for elimination, there is no label on the work area, there is no regular cleaning, employees do not understand 5s, there are no procedures and 5s standards, there is no audit regarding 5s, there is no visual management system and standard procedures regarding 5s, lots of garbage scattered, dirty work surfaces and difficult to clean, everyone is not involved in 5s activities; 2) The results of the 5S assessment before improvement were 37.78% in the bad category. After planning the implementation of the improvement, the score rose to 80% in the good category